Power and law: asymmetric balancing between China, the US, and Southeast Asian claimants in the South China Sea and the subregional order, 2010-2021 - Liu, Yue (The University of Edinburgh, 2024)
Tensions in the South China Sea (SCS) have significantly escalated since 2010. They have developed from territorial and maritime disputes among littoral states to complicated issues covering sovereignty, jurisdiction, resources, geopolitics, and international law. China has stepped up efforts to fulfil territorial claims in the SCS and made significant achievements. The United States has deepened its intervention in the SCS disputes and security. The Philippines initiated an international arbitration (2013–2016) against China, challenging China’s nine–dash line claim and maritime activities. China and the Association of Southeast Asian Nations (ASEAN) have endeavoured to negotiate a Code of Conduct (CoC) under international law to manage tensions in the SCS. Against this background, it is puzzling that weaker Southeast Asian claimants have not always deferred to/bandwagon with their powerful counterpart, China, despite the widened economic and military disparities, which would be inconsistent with Asymmetry theory’s expectation (Womack, 2006). Neither have they taken firm actions to balance China’s growing power in the SCS despite the enlarged system disequilibrium, which would be out of traditionally Western–centric theories’, notably realism’s anticipation (Hans J. Morgenthau, 1973; Waltz, 1979). This thesis aims to resolve the puzzle of why Southeast Asian claimants’ behaviours have not aligned with the expectations of certain elements of IR theories. Doing so requires examining how, and with what outcomes, the forces of power politics and international law have interacted to steer state interactions and order in the SCS since 2010. It further expands to three interrelated questions. First, how has China exerted its power to advance territorial claims in the SCS, and in what ways has it promoted an asymmetric subregional order? Second, how has the US penetrated its power in the SCS, and in what ways has it influenced asymmetric order in this subregional system? Third, how has international law contributed to solving the SCS disputes, and in what ways has it impacted asymmetric order in this subregional system? To carry out the investigation, this thesis adopts qualitative methods, using documentary research for data collection and content analysis for data analysis. The selected objects are China, the US, and Southeast Asian claimants: Vietnam, Malaysia, Indonesia, Brunei, and the Philippines. The timeline focuses on 2010–2021, from when both China and the US upgraded the strategic importance of the SCS to when it was approaching the end of US President Donald Trump’s term. Besides, it looks back to the time before 2010 and keeps an eye on the dynamics after 2021 until the completion of this thesis because the SCS problem is historical and ongoing. It adopts an interdisciplinary approach, incorporating International Relations (IR) and International Law (IL). This thesis combines Asymmetry and Regional Security Complex (RSC) theories and uses both political and legal analytical tools to build a composite theoretical framework for unravelling the relevant states’ interactions in the SCS and their influence on subregional order. Asymmetry (Womack, 2006) and RSC (Buzan & Wæver, 2003) theories shed different light on the problem under investigation, but neither is sufficient. The former is an Asian–driven theory assuming a hierarchical order. The latter is developed from traditionally Western–oriented realism, liberalism, and constructivism that take anarchy for granted. This thesis conciliates the two different perspectives about the structural nature of international systems, maintaining that the SCS subregional system is fundamentally asymmetric/hierarchical but anarchic to a certain degree. It argues that since 2010, power politics and international law have become two forces intertwined to form an “asymmetric balancing” model characterising the interactions between China, the US, and Southeast Asian claimants in the SCS subregional system. It has shaped a hybrid asymmetric order, essentially hierarchical but presenting some anarchic characters. It further argues that the rapidly enlarged power disparities between China and Southeast Asian claimants have prompted the SCS asymmetry, which is relatively peaceful and stable, crediting to normalcy management by littoral states. The US superpower penetration in the SCS has generated power–balancing effects on the system, weakening the base of the SCS asymmetry militarily. International law has brought legal–balancing effects on the system, weakening the normative base of the asymmetry. Power and legal balancing forces have prompted the SCS subregional system to morph into a hybrid one presenting not only hierarchical but also anarchic features, including alliance behaviours (between the US and Southeast Asian claimants), great power competition (between the US and China), sovereign equality principles. However, they have not fundamentally altered the asymmetric/hierarchical nature of the system’s order because the power gap and the inequalities between China and Southeast Asian claimants are profound. This thesis makes unique contributions to studying state interactions and order in the SCS and IR. First, it develops IR theories by combining multiple theories and different disciplinary perspectives to create a hybrid theoretical framework, in which it proposes three new concepts: “asymmetric balancing”, “legal balancing”, and “hybrid asymmetric order”. They advance the explanation of the hybridity in interactions between China, the US, and Southeast Asian claimants in the SCS and the subregional order, which presents both hierarchy and anarchy and is shaped by both power–political and legal forces. These concepts can also be applied beyond the SCS scenario, explaining state interactions in other cases that present hybridity. Second, this thesis advances the application of the RSC theory’s “superpower penetration” concept by applying it to examine US engagement in the SCS and its implications on subregional security and order. This extends the theoretical application of this notion in a new case and offers novel empirical experience to develop it. Third, this thesis adds new knowledge to the SCS study field and IR by exploring the historical asymmetry in Southeast Asia and the regional uniqueness, weighing more on Southeast Asian claimants’ approach to major powers and their role in shaping the SCS order, and incorporating scholarship in IL.
Keywords: Southeast Asia; Maritime Law; international security; international order; geopolitics; maritime disputes; international arbitration; international relations; international relations theory